Values of Islamic Education in The Sekujang Tradition of Serawai Bengkulu (Historical Study) - Monita, Diana; Hasan, Moh. Ferdi (Proceeding International Conference on Religion, Science and Education, 2024)
This research is motivated by the many cultures and traditions in Indonesia which are caused by multiculturalism, one of which is the sekujang culture in the Serawai tribe, Kepahiang district, Bengkulu province and the values of Islamic education contained therein. This research is a type of qualitative research based on field research and uses data collection methods in the form of interviews and observations which are then analyzed descriptively-normatively. Researchers are very interested in this research because they see a close relationship of friendship shown in the celebration of this sekujang tradition which until now has always been held by the Serawai tribe every Eid celebration. The purpose of this research is to see what are the values of Islamic education contained in sekujang culture that are very relevant to Islamic teachings. The researcher found that there were several values of Islamic education in the Sekujang culture of the Serawai tribal people of Kepahiang Bengkulu district and classified them into three aspects, namely religious aspects, personality aspects and social aspects.